The Bushmen and their stories - Helfman, Elizabeth S; Cuffari, Richard, 1925- (New York : Seabury Press, 1971)
Brief discussions of the philosophy and way of life of the African Bushmen serve as background for retellings of seventeen folktales of these desert people.
Keywords: San (African people) -- Folklore; Tales -- Africa, Southern